Dinamika Kadar Protein Dan Aktivitas Protease Cairan Rumen Domba Lokal Yang Diberi Fodder Jagung Hidroponik Dan Hijauan Lain Secara Invitro - Faradha, Rifky; Suryapratama, Wardhana; Rahayu, Sri (ANGON: Journal of Animal Science and Technology, 2019)
Background. The aim of research was to examine the effect of hydroponic maize fodder and other forage towards Dynamics Protein Level and Enzym Protease Activity Digestive Rumen Sheep using In-Vitro Method. Materials and methods. The material that used in this research were three digestive rumen ofsheep. The research was held from January 14th, 2018 to March 7th, 2018 at the Laboratory of Science Feed and Nutrition, Faculty of Animal Science,JenderalSoedirman University, Purwokerto, Indonesia with in vitro method. The research was designed by Completed Randomized Design (CRD). The data was analyzed with analysis of variance (anova) and further testing by Honesty Significant Difference (HSD) test. The treatment consist of P1= 60 % Concentrate + 40 % Hydroponic Maize Fodder, P2 = 60 % Concentrate + 40 % Conventional Maize fodder, P3 = 60 % Concentrate + 40 % grass field and 6 repetition with 0 hours, 8 hours, 16 hours, 24 hours incubation. Data variable that measured are dynamics protein level and enzym protease activity. The result based on the test showed that provision of hydroponic maize fodder produce the highest dynamics protein level which is 0.0419 at the 8th hour of incubation compared to conventional maize fodder and field grasses. Results. Based on the results of the analysis of variance showed that the treatment of feeding various types of forages at a measurement of 0 hours of real incubation resulted (P<0.05) in the highest protease activity. Utilizing of hydroponic maizefodder and maize fodder as a forage source produced the highest protease activity compared to field grass. The average of dynamics protein level basedon the treatment research P1, P2, dan P3from 8 hours, 16 hours, and 24 hours of incubation consecutively was 0.0206; 0.0079; 0.0026 percent per hours,0.0056; 0.0109; 0.0139 percent per hours, 0.0020; 0.0031; 0.0080 percent per hours. The average of protease activity based on the treatment research P1, P2,dan P3 from 0 hours, 8 hours, 16 hours, and 24 hours of incubation consecutively was 0.972; 1.107; 0.918 U/mg, 1.020; 0.965; 1.030 U/mg, 1.005; 0.947; 1.040 U/mg, 1.120; 0.978; 0.972 U/mg. Conclusion The highest protein dynamics level were seen in the hydroponic maize fodder treatment (P1) then followed by fodder maize treatment (P2) and field grass. Protease activity in fodder maize treatment (P2) showed the highest value followed by the treatment of hydroponic maize fodder (P1) then the lowest was the field grass treatment (P3).